An Innovative Flexible Investment Vehicle Oriented to Sustainability – The Adaptation of Hedge Funds in the Case of Emerging Markets - Gabriela Prelipcean; Mircea Boscoianu (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
The problem of investments oriented on sustainability in emerging markets is actual and complex and should be carefully analysed in order to offer the optimal strategies. The sustainable investments based on ESG (environmental – social - governance) criteria could better respond to the global market drivers (the interest on environmental concerns, the spectral dynamics of energy prices, the speed of technological change) with impact on the design of new business models. The interest is to find an effective and efficient strategy and a vehicle capable to mobilize a critical mass of investment funds oriented in sustainability in the new context of Industry 4.0. The proposal to introduce socially responsible investment funds (SRIF) as a new investment area and hedge fund, as the structure of alternative investments in emerging markets is an absolute novelty for Romania, in the context of a capital market that only in 2020 it move to emerging market status. Putting into practice through effective implementation is possible considering specific adaptation elements presented in this proposal.
Keywords: O16; G23; G24; Q01; 330; innovative investment vehicle; socially responsible investment funds (SRIF); hedge fund in emerging markets (HF-EM); active risk management